2009
DOI: 10.1016/j.jhazmat.2008.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of plant growth and nickel uptake by nickel resistant-plant-growth promoting bacteria

Abstract: In this study, among a collection of Ni-resistant bacterial strains isolated from the rhizosphere of Alyssum serpyllifolium and Phleum phleoides grown on serpentine soil, five plant growth-promoting bacteria (PGPB) were selected based on their ability to utilize 1-aminocyclopropane-1-carboxylate (ACC) as the sole N source and promote seedling growth. All of the strains tested positive for indole-3-acetic acid (IAA) production and phosphate solubilization. In addition, four of the strains exhibited significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 199 publications
(74 citation statements)
references
References 70 publications
2
68
1
3
Order By: Relevance
“…Compared with non-inoculated control treatment,inoculation of RC6b for 7 d, significantly increased the concentrations of water soluble Cd, Zn and Pb in soil by 16.7-, 4.6-and 5.7-fold, respectively. These results are consistent with those of Jiang et al (2008) and Rajkumar et al (2008) and Ma et al (2009), they found an increase in metal concentrations (Ni, Cu, Zn, Cd and Pb) in water soluble fractions in the presence of metal mobilizing bacteria. The observed increase in the concentrations of water soluble metals in this study could be attributed to the effects of microbial metabolites/actions such as altering soil pH, release of organic acids, siderophores and oxidation/reduction reactions (Rajkumar et al, 2012(Rajkumar et al, , 2013.…”
Section: Isolation Of Metal Mobilizing Bacteriasupporting
confidence: 92%
See 3 more Smart Citations
“…Compared with non-inoculated control treatment,inoculation of RC6b for 7 d, significantly increased the concentrations of water soluble Cd, Zn and Pb in soil by 16.7-, 4.6-and 5.7-fold, respectively. These results are consistent with those of Jiang et al (2008) and Rajkumar et al (2008) and Ma et al (2009), they found an increase in metal concentrations (Ni, Cu, Zn, Cd and Pb) in water soluble fractions in the presence of metal mobilizing bacteria. The observed increase in the concentrations of water soluble metals in this study could be attributed to the effects of microbial metabolites/actions such as altering soil pH, release of organic acids, siderophores and oxidation/reduction reactions (Rajkumar et al, 2012(Rajkumar et al, , 2013.…”
Section: Isolation Of Metal Mobilizing Bacteriasupporting
confidence: 92%
“…The bacterial growth was monitored by measuring the OD at 600 nm. Further, the ACC deaminase activity was determined as described by Ma et al (2009). Siderophore production by metal mobilizing strain was detected by the method of Schwyn and Neilands (1987) using chrome azurol S (CAS) agar.…”
Section: Characterization Of Plant Growth Promoting Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of certain metal resistant microorganisms like Psychrobacter sp. SRA1, Bacillus cereus SRA10, Bacillus weihenstephanensis SRP12, Sphingomonas macrogoltabidus and Microbacterium liquefaciens, can affect the trace metal mobility and availability to the plants through release of chelating agents, acidification, phosphate solubilization and redox changes (Abou-Shanab et al, 2003;Idris et al, 2004;Ma et al, 2009).…”
Section: Introductionmentioning
confidence: 99%